Maternal and fetal outcomes of lupus pregnancies: A collective effort by Karnataka Rheumatologists. (October 2020) - Janardana, Ramya; Haridas, Vikram; Priya, Vishnu; Bhat, Vasudha; Singh, Yogesh; Rao, Vijay K; Jois, Ramesh; Srikantiah, Chandrashekara; Pinto, Benzeeta; Shobha, Vineeta
Introduction: Identifying factors predicting adverse pregnancy outcomes involving systemic lupus erythematosus (SLE) is a research priority. The aims of this study were to investigate (a) the maternal and fetal outcomes of pregnant lupus patients and the factors associated with adverse pregnancy outcomes, and (b) the effect of pregnancy on lupus disease activity of these patients. Methods: This was an ambi-directional study collecting information from five multi-specialist referral centres across the state of Karnataka, India over 5 years (2013–2018). Clinical details of pregnancies and outcomes that were temporally associated with lupus disease were recorded using a structured pro forma. The Safety of Estrogen in SLE National Assessment-SLE Disease Activity Index (SELENA-SLEDAI) was used to assess lupus activity during the 6 months prior to pregnancy and the intra- and post-partum periods. Modifications suggested in the SLE Pregnancy Disease Activity Index were considered while scoring. Results: A total of 121 pregnancies in 80 SLE patients with a mean age of 27.1 (±4.5) years and with a mean disease duration of 4.6 (±4.1) years were reviewed. Largely patients were in clinical remission (109/121; 90.1%). Antiphospholipid antibody positivity was seen in 45/121 (37.2%) patients. A history of lupus nephritis was noted in 29/121 (24%) patients. Maternal complications (32%) were mainly due to hypertensive disorders of pregnancy (HDP; 19/121; 15.7%). Adverse fetal outcomes (58%) were mainly in the form of spontaneous first-trimester abortions (21/121; 16%), stillbirth (14/121; 11.6%) and prematurity (24/121; 20%). HDP is strongly associated with stillbirth and prematurity and is independent of active lupus. Disease activity was associated with a three-fold increased risk of adverse fetal outcome in univariate analysis. The risk of major flare during pregnancy is low (4.1%) when conception occurs during stable disease. Hydroxychloroquine (HCQ) use was associated with reduced risk of flare ( p  = 0.001) in patients in remission at the time of conception. Conclusions: The risk of major flare during pregnancy is low when conception happens during stable disease. HCQ use was associated with reduced risk of flare in patients in remission at the time of conception. HDP was strongly associated with stillbirth and prematurity and are independent of active lupus in our cohort.